Sistem Informasi Mobile Kosan Berbasis Android - Amirudin Wibowo (Jurnal Ilmu Teknik dan Komputer, 2020)
The increasing number of residents coming from outside Jabodetabek has resulted in increased activity in the Jabodetabek area. Generally newcomers are reluctant to have permanent housing but prefer semi-permanent buildings such as boarding houses, so that newcomers make boarding houses a flexible place to live. What must be considered in the selection of boarding houses in addition to the available prices and facilities is also because if newcomers want to find a boarding house must see the distance so they can estimate how much time the boarding house goes to the intended place such as campus or office harmed as well as environmental conditions so as to create a comfortable and peaceful atmosphere. Newcomers must be able to socialize with local residents so that harmony can be maintained, for example following a mutual cooperation activity held once a month to strengthen the relationship. One that makes it easier for newcomers to find a boarding house is to make a mobile android based application considering that it is quite fast in this modern era, the access can easily be done anywhere and whenever needed. The information needed is the name of the owner of the boarding house, room data. facilities, location and price..